Design a System for Calculating the Number of People Passing Using the Arduino Uno Based PIR (Passive Infrared Receiver) Sensor - Muhammad Yakob; Rachmad Almi Putra; Hendri Saputra; Miranda Miranda; Fajriani Fajriani (Jurnal Pendidikan Fisika, 2019)
This study aims to build a system of counting people in the center of the crowd. This system uses PIR sensors to detect human movements so that the number of people passing through these sensors can be counted. The design of this tool uses hardware and software. The hardware used is like Arduino, PIR sensors, and also LEDs, while software uses programs arranged to adjust commands that will be sent to hardware. This tool is made by using two PIR sensors, where the first sensor is the marker of the person entering and the second sensor as a marker of people coming out. When the first sensor detects a person, the number of people passing through the sensor will be +1, when the second sensor detects a person, the number of people passing sensor -1.Keywords: Pir, Arduino, Infrared, Receiver, SensorPenelitian ini bertujuan untuk membangun sistem penghitungan orang di tengah keramaian. Sistem ini menggunakan sensor PIR untuk mendeteksi pergerakan manusia sehingga jumlah orang yang melewati sensor ini dapat dihitung. Desain alat ini menggunakan perangkat keras dan perangkat lunak. Perangkat keras yang digunakan seperti Arduino, sensor PIR, dan juga LED, sedangkan perangkat lunak menggunakan program yang dapat diatur menyesuaikan perintah yang akan dikirim ke perangkat keras. Alat ini dibuat dengan menggunakan dua sensor PIR, dimana sensor pertama adalah penanda orang yang masuk dan sensor kedua sebagai penanda orang keluar. Ketika sensor pertama mendeteksi seseorang, jumlah orang yang melewati sensor akan +1, ketika sensor kedua mendeteksi seseorang, jumlah orang yang melewati sensor -1.Kata kunci: Pir, Arduino, Infrared, Receiver, Sensor